2015
DOI: 10.1007/s11356-015-4716-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of phosphogypsum on growth, physiology, and the antioxidative defense system in sunflower seedlings

Abstract: Phosphogypsum (PG) is the solid waste product of phosphate fertilizer production and is characterized by high concentrations of salts, heavy metals, and certain natural radionuclides. The work reported in this paper examined the influence of PG amendment on soil physicochemical proprieties, along with its potential impact on several physiological traits of sunflower seedlings grown under controlled conditions. Sunflower seedlings were grown on agricultural soil substrates amended with PG at rates of 0, 2.5, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 68 publications
3
13
0
Order By: Relevance
“…GST together with xenobiotic substances catalyzes the conjugation of GSH and plays an important role in detoxification [31]. Studies already exist showing that GST and GR activities change at sunflower exposed to different stresses [13,14,23,44]. In the present study, GST and GR enzyme activities were shown to be increased all stress groups, compared to control.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…GST together with xenobiotic substances catalyzes the conjugation of GSH and plays an important role in detoxification [31]. Studies already exist showing that GST and GR activities change at sunflower exposed to different stresses [13,14,23,44]. In the present study, GST and GR enzyme activities were shown to be increased all stress groups, compared to control.…”
Section: Discussionsupporting
confidence: 62%
“…GR plays a major role in cell defense against oxidative stress. It efficiently maintains the reduced pool of GSH [14]. GST together with xenobiotic substances catalyzes the conjugation of GSH and plays an important role in detoxification [31].…”
Section: Discussionmentioning
confidence: 99%
“…cathayana cutting roots was suppressed by salt stress, which was mainly due to the direct effect of salt stress on fungi. Salt stress could hamper the colonization capacity by inhibiting spore germination27, hyphal growth in soil25 and hyphal spread after initial colonization9.…”
Section: Discussionmentioning
confidence: 99%
“…All these impacts contribute to stunted growth and production losses. Plants have various strategies to adapt to or avoid the damages caused by the activation of reactive oxygen species (ROS) and the accumulation of osmotic regulators89. That ROS generation and its scavenging system have a key effect in the defense of plants against various stresses has been well-documented1011.…”
mentioning
confidence: 99%
“…The direct and indirect discharges of industrial and urban wastes have resulted in the chemical contamination of the soil by organic pollutants and HMs (Sun et al, 2012;Elloumi et al, 2015). The presence of HMs in sewage sludge (SS), used as agricultural fertilizer is a major problem for soil and crop qualities.…”
Section: Introductionmentioning
confidence: 99%